(untitled) (Fiep Bulletin - online, 2016)
Skin cancer is the most common in humans, accounting for one third of all cancer cases in the world. This study aimed to know the theoretical work about the farm worker profile and meet plans for preventing skin cancer, from the nursing professional. For its realization, an integrative review including papers was necessary, and research-based Virtual Health Library (VHL), and digital banks between the years 2009 to 2014. Of the 21 selected articles they indicated the prevalence of cancer skin rural workers. The studies showed that the past five years, has significantly increased the rate of cases of skin cancer, especially in rural workers. It is hoped that measures to prevent skin cancer in farm workers are taken, considering the constant exposure to sunlight and the need to interact with the work of the nursing staff with the capacity to offer plans of prevention and care in an attempt to provide better results for the working class.